ATOMS: ALMA three-millimeter observations of massive star-forming regions – VII. A catalogue of SiO clumps from ACA observations. Issue 3 (14th January 2022) - Liu, Rong; Liu, Tie; Chen, Gang; Liu, Hong-Li; Wang, Ke; Li, Jin-Zeng; Lee, Chang Won; Liu, Xunchuan; Juvela, Mika; Garay, Guido; Dewangan, Lokesh; Soam, Archana; et al.
ABSTRACT: To understand the nature of SiO emission, we conducted ACA observations of the SiO (2-1) lines toward 146 massive star-forming regions, as part of the ALMA Three-millimeter Observations of Massive Star-forming regions (ATOMS) survey. We detected SiO emission in 128 (87.7${{\ \rm per\ cent}}$ ) sources and identified 171 SiO clumps, 105 of which are spatially separated from 3 mm continuum emission. A large amount of the SiO line profiles (60${{\ \rm per\ cent}}$ ) are non-Gaussian. The velocity dispersion of the SiO lines ranges from 0.3 to 5.43 km s −1 . In 63 sources the SiO clumps are associated with H ii regions characterized by H40α emission. We find that 68${{\ \rm per\ cent}}$ (116) of the SiO clumps are associated with strong outflows. The median velocity dispersion of the SiO line for outflow sources and non-outflow sources is 1.91 km s −1 and 0.99 km s −1, respectively. These results indicate that outflow activities could be connected to strongly shocked gas. The velocity dispersion and [SiO]/[H 13 CO + ] intensity ratio do not show any correlation with the dust temperature and particle number density of clumps. We find a positive correlation between the SiO line luminosity and the bolometric luminosity, implying stronger shock activities are associated with more luminous protoclusters. The SiO clumps in associations with H ii regions were found to show a steeper feature in $L_{\rm{sio}}$ /$L_{\rm{bol}}$ . The SiO line luminosity and the fraction of shocked gas have no apparent evidence of correlation with the evolutionary stages traced by luminosity to mass ratio ($L_{\rm{bol}}/M$ ).